Analysis of Income Organik Rice Farmers in Nagari Kamang Mudiak Village Kamang Magek Sub-District Agam Regency West Sumatera - Amelia, Titin; Eliza, Eliza; Edwina, Susy (Politeknik Pertanian Negeri Payakumbuh, 2021)
The Rice plant is one of the leading commodities in agriculture, considering that rice is one of the staple foods of Indonesian society. In addition, rice is the main source of income in the highlands. This study aims to analyze the net income of farmers and the efficiency of lowland rice farming. This research is conducted in Kamang Mudiak village, Kamang Magek Sub-district, Agam Regency, West Sumatra. The research is conducted using a survey method with census sampling of 30 organic rice farmers. The results showed that there were several differences in rice cultivation which was carried out organically and inorganically which had been carried out by farmers. The difference between organic and inorganic cultivation is in the type of fertilizer used. However, the water used in the cultivation of rice plants is the same, because, in the research area, rainwater is used to irrigate crops and can also be called rainfed rice fields. The research area does not use pesticides to eradicate pests or diseases, be it organic rice cultivation or inorganic rice cultivation. However, if you use pesticides, of course, there are also differences. The results show that there are several differences in the cultivation of rice which is carried out organically and inorganically by farmers. The difference between organic and inorganic cultivation is the type of fertilizer used. Organic cultivation uses fertilizers that contain easily broken down ingredients such as compost, goat urine, and vegetable ingredients. In addition, there is an increase in the production of unhulled rice from the production of organic cultivation, which reaches a production of 7,163.80 Kg / MT / Ha. The increase in production causes a total net income from organic unhulled production of Rp. 18,495,832.36 / MT / Ha. The RCR value of this farm is 1.94, which means that the farming carried out by the farmer is profitable and it can be considered efficient because the RCR value obtained is more than one (RCR grater than 1).